2021
DOI: 10.1186/s41476-021-00171-w
|View full text |Cite
|
Sign up to set email alerts
|

Drastic advancement in nanophotonics achieved by a new dressed photon study

Abstract: On the very recent advancement of dressed photon studies A timely review of the emerging new phase of dressed photon (DP) studies, not yet prevailing in the global nanophotonic society, is given in contradistinction to its preceding incipient phase. A new theory on DPs crucially depends on a couple of important elements, namely, the knowledge on quantum field theory (QFT) having infinite degrees of freedom, notably on the micro-macro duality (MMD) theory developed by Ojima, and a newly proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Cross-correlation coefficient These two features suggest the possibility that an emitted cluster of photons behaves as if it is a single photon. This possibility can be conjectured to be related to the localizable property of the spin-zero particle we noted [43] in relation to the Wightman theorem [45]. Namely, if the observable positions of given spin-zero quantum particles are sufficiently close, then the cluster of these particles would behave as if it is a single quantum particle with the accumulated amount of energy.…”
Section: Time Difference (Ns)mentioning
confidence: 86%
See 2 more Smart Citations
“…Cross-correlation coefficient These two features suggest the possibility that an emitted cluster of photons behaves as if it is a single photon. This possibility can be conjectured to be related to the localizable property of the spin-zero particle we noted [43] in relation to the Wightman theorem [45]. Namely, if the observable positions of given spin-zero quantum particles are sufficiently close, then the cluster of these particles would behave as if it is a single quantum particle with the accumulated amount of energy.…”
Section: Time Difference (Ns)mentioning
confidence: 86%
“…The contents of electromagnetism in this section and of novel cosmology in the subsequent section are the epitome of our series of recent studies reported in several papers. The latest research outcomes in the respective fields were reported by Sakuma et al [43,58].…”
Section: Spacelike Maxwell's Field and A Novel Dp Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In their recent study on the off-shell properties of quantum fields motivated by enigmatic dressed photon research, 10 Sakuma et al 23,27 shed new light on the longforgotten GR theory (proved in axiomatic QFT) referred to in the introduction, which states that interactions among quantum fields must inevitably accompany spacelike momentum supports. Since these findings revealed a novel perspective on cosmology, especially for models of dark energy and dark matter, we will briefly review these findings before we discuss the abovementioned dark matter model Ωu µ further.…”
Section: Brief Review Of Previous Cosmological Studies By Sakuma Et Almentioning
confidence: 99%
“…We investigated this form because the important scalar parameter in our dark matter model must be identified in terms of the "zeropoint energy"of the Ω field, which exists implicitly in the quantum version of Eq. (10).…”
Section: On the Flatness Of The Universe And The Thermodynamic Twin S...mentioning
confidence: 99%